The importance of lymph node dissection accompanying wedge resection for clinical stage IA lung cancer†. (15th December 2016) - Stiles, Brendon M.; Kamel, Mohamed K.; Nasar, Abu; Harrison, Sebron; Nguyen, Andrew B.; Lee, Paul; Port, Jeffrey L.; Altorki, Nasser K.
Abstract: OBJECTIVES: For patients undergoing lobectomy for non-small cell lung cancer (NSCLC), a survival benefit exists with increased number of lymph nodes (LNs) resected. We sought to evaluate the associations of LN removal with outcomes in clinical stage I lung cancer patients undergoing wedge resection. METHODS: We evaluated all patients undergoing wedge resection for peripheral, clinical stage IA NSCLC and grouped patients into those with and without LN assessment. Data were compared and survival analysed using Kaplan–Meier, with differences compared using log-rank. Propensity score matching controlling for age, gender, Charlson comorbidity index, patient tolerability of lobectomy, surgery year, tumour size and surgical approach was done (51 patients in each group, caliper 0.2) RESULTS: We identified196 patients undergoing wedge resection, of whom 138 patients (70%) had LNs resected (median = 4 nodes), while the remaining 58 patients (30%) had none. There were no significant differences in the clinical or pathologic characteristics between the two groups. There was no difference in terms of OR time, estimated blood loss, chest tube duration or length of stay. Median pT size was 1.5 cm in each group ( P  = 0.73). Among patients with LNs removed, 6 (4.3%) had positive nodes Patients in the LN assessed group had higher probability of freedom from loco-regional recurrence compared to the no lymph node (NLN) group (5-year: 92 vs 74%, P  = 0.025).In propensity matched groups, patients who underwent LN dissection also had higher probability of freedom from local recurrence ( P  = 0.024). CONCLUSIONS: Accompanying wedge resection for lung cancer, LN sampling adds no morbidity and does not increase length of stay. Positive nodes are identified in 4.3% of patients thought eligible for wedge resection. LN removal appears to decrease locoregional recurrence and may be associated with a survival benefit.